Oxidative Stress Biomarkers and Incidence of Postoperative Atrial Fibrillation in the Omega‐3 Fatty Acids for Prevention of Postoperative Atrial Fibrillation (OPERA) Trial. Issue 5 (May 2015) - Wu, Jason H. Y.; Marchioli, Roberto; Silletta, Maria G.; Masson, Serge; Sellke, Frank W.; Libby, Peter; Milne, Ginger L.; Brown, Nancy J.; Lombardi, Federico; Damiano, Ralph J.; Marsala, Joann; Rinaldi, Mauro; et al.
Abstract : Background: Animal study results point to oxidative stress as a key mechanism triggering postoperative atrial fibrillation (PoAF), yet the extent to which specific biomarkers of oxidative stress might relate to PoAF risk in humans remains speculative. Methods and Results: We assessed the association of validated, fatty acid–derived oxidative stress biomarkers (F2 ‐isoprostanes, isofurans, and F3 ‐isoprostanes) in plasma and urine, with incident PoAF among 551 cardiac surgery patients. Biomarkers were measured at enrollment, the end of surgery, and postoperative day 2. PoAF lasting ≥30 seconds was confirmed with rhythm strip or electrocardiography and centrally adjudicated. Outcomes were assessed until hospital discharge or postoperative day 10, whichever occurred first. Urine level of each oxidative stress biomarker rose at the end of surgery (2‐ to 3‐fold over baseline, P <0.001) and subsequently declined to concentrations comparable to baseline by postoperative day 2. In contrast, plasma concentrations remained relatively stable throughout the perioperative course. Urine F2 ‐isoprostanes and isofurans at the end of surgery were 20% and 50% higher in subjects who developed PoAF ( P ≤0.009). While baseline biomarker levels did not associate significantly with PoAF, end of surgery and postoperative day 2 isoprostanes and isofurans demonstrated relatively linear associations with PoAF. For example, the end of surgery extreme quartile multivariate adjusted OR (95% CI) for urine isofurans and F3 ‐isoprostanes were 1.95 (1.05 to 3.62; P for trend=0.01) and 2.10 (1.04 to 2.25, P for trend=0.04), respectively. The associations of biomarkers with PoAF varied little by demographics, surgery type, and medication use ( P ≥0.29 for each). Conclusions: These novel results add to accumulating evidence supporting the likely key pathogenic role of elevated oxidative stress in PoAF. Clinical Trial Registration: URL:Clinicaltrials.gov Unique identifier: NCT00970489.